Simple Triage and Rapid Treatment (START) Health Education Method To Preparedness Nurse of Public Health Center (Puskesmas) - Yeni Rimadeni; Munazar Munazar; Arnisam Arnisam; Manovri Yeni (UNIVERSITAS SERAMBI MEKKAH, 2021)
Limited human resources turn triage into an unavoidable solution in disaster management. Simple Triage and Rapid Treatment (START) is a triage method that is widely accepted and easy to use to handle disasters with a time of 30 seconds or less based on three primary examinations such as respiration, checking the radial pulse, mental status. This study aims to identify differences in the preparedness of nurses at the Puskesmas at Kaki Gunung Burni Telong Kabupaten Bener Meriah Regency before and after the health education method intervention (START). The data sources for this study were the nurses of the puskesmas at Kaki Gunung Burni Telong Kabupaten Bener Meriah totaling 20 people. The research design used a quasi-experiment